pengaruh PENGARUH FINGER PAINTING TERHADAP KETERAMPILAN MOTORIK HALUS ANAK CEREBRAL PALSY DI LAYANAN TERAPI INCLUSIVE CENTER KECAMATAN KARANGANOM KABUPATEN KLATEN PROVINSI JAWA TENGAH: Finger painting - Hanifah, Nina; Sari, Erma Kumala; Prakosha, Donni (JPI (Jurnal Pendidikan Inklusi), 2022)
This study aims to determine the effect of finger painting activities on the fine motor skills cerebral palsy in inclusive center therapy services in Kecamatan Karanganom, Kabupaten Klaten. This research uses quantitative methods with Single Subject Research (SSR). The design used in this study was A1-B-A2 or baseline1 – intervention – baseline2. The subject used in this study was a cerebral palsy child in the inclusive center therapy service in Kecamatan Karanganom, Kabupaten Klaten. The technique used in data collection is a performance test with 21 questions. The validity test uses the content validity test. This study used inter-ratter reliability. The assessment instruments in this study have been validated to three experts in the fields of materials, media and measurement. The data from the study were analyzed using descriptive analysis presented in the form tables and graphs using analysis components in conditions and between conditions. The results showed an increase in fine motor skills through finger painting activities with a mean at baseline1 of 49,31, intervention of 62,32 and baseline2 of 73,33. Based on the results this study, it can be concluded that finger painting activities have an effect on improving fine motor skills of cerebral palsy children in inclusive center therapy services in Kecamatan Karanganom Kabupaten Klaten.